Customizable Life Cycle Cost Methodology for Ammonia Fuel Storage: Enhancing Adoptability Across Diverse Onboard Arrangements - Evanthia Kostidi; Dimitrios Lyridis (Energies)
While ammonia offers several benefits as an alternative fuel, its adoption poses significant technical and economic challenges, particularly with respect to onboard storage and handling. To facilitate the large-scale deployment of ammonia in marine applications, there is a critical need to develop a robust methodology for assessing the life cycle costs of ammonia storage systems on vessels, either new-build and retrofit installations. With a robust life cycle cost analysis (LCCA) methodology, the maritime industry can better evaluate the feasibility of onboard ammonia storage systems, paving the way for their large-scale adoption and supporting global efforts to reduce carbon emissions. Given that ammonia is a relatively new marine fuel, this work addresses the current gap in knowledge by offering a structured approach to evaluating the costs across the entire life cycle of an onboard ammonia storage system, including design, construction, operation, maintenance, and end-of-life decommissioning. This methodology was developed with a high degree of flexibility to accommodate uncertainties in both technological alternatives and cost estimation. This work offers significant contributions to both academia and industry by establishing a replicable and adaptable LCCA framework for assessing storage solutions.